Technological business strategies for environmental sustainability among Asia-Pacific Economic Cooperation forum (APEC) member states: a bibliometric study (Journal of Business, Universidad del Pacífico (Lima, Peru), 2022)
The implementation of sustainable development within the member states of the Asia-Pacific Economic Cooperation forum (APEC) takes into account business technologies and strategies as key to progress. As such, this paper proposes a methodology for a systematization of the literature that recognizes the importance and growth of the topic over time. It encompasses an analysis of the countries with the greatest scientific output, the most productive authors, and a characterization of the areas and variables researched, as well as some possible future lines of research. The bibliometric analysis was based on a review of 234 scientific papers in the Scopus database. The main results reveal increasing interest in information systems and technologies in relation to environmental problems, with interdisciplinary perspectives to environmental sustainability.
Keywords: technology; business strategies; APEC; environmental sustainability; bibliometrics